BONLAC: A combinatorial proteomic technique to measure stimulus-induced translational profiles in brain slices. (January 2016) - Bowling, Heather; Bhattacharya, Aditi; Zhang, Guoan; Lebowitz, Joseph Z.; Alam, Danyal; Smith, Peter T.; Kirshenbaum, Kent; Neubert, Thomas A.; Vogel, Christine; Chao, Moses V.; Klann, Eric
Abstract: Stimulus-triggered protein synthesis is critical for brain health and function. However, due to technical hurdles, de novo neuronal translation is predominantly studied in cultured cells, whereas electrophysiological and circuit analyses often are performed in brain slices. The different properties of these two experimental systems create an information gap about stimulus-induced alterations in the expression of new proteins in mature circuits. To address this, we adapted two existing techniques, BONCAT and SILAC, to a combined proteomic technique, BONLAC, for use in acute adult hippocampal slices. Using BDNF-induced protein synthesis as a proof of concept, we found alterations in expression of proteins involved in neurotransmission, trafficking, and cation binding that differed from those found in a similar screen in cultured neurons. Our results indicate important differences between cultured neurons and slices, and suggest that BONLAC could be used to dissect proteomic changes underlying synaptic events in adult circuits. This article is part of the Special Issue entitled 'Synaptopathy – from Biology to Therapy'. Graphical abstract: Highlights: BONLAC is a combinatorial proteomic screening method based on BONCAT and SILAC. BONLAC detects de novo translation in brain slices over short time scales. Consistency scores reliably identify protein candidates in BONLAC screens. BONLAC reveals BDNF-induced synthesis of proteins involved in synaptic transmission. BDNF-induced proteomic candidates differ between brain slices and cultured neurons.